Epidemiology of Coxiella burnetii infection in Africa: a OneHealth systematic review. - Sky Vanderburg; Matthew P Rubach; Jo E B Halliday; Sarah Cleaveland; Elizabeth A Reddy; John A Crump (PLoS Neglected Tropical Diseases, 2014)
Background Q fever is a common cause of febrile illness and community-acquired pneumonia in resource-limited settings. Coxiella burnetii, the causative pathogen, is transmitted among varied host species, but the epidemiology of the organism in Africa is poorly understood. We conducted a systematic review of C. burnetii epidemiology in Africa from a "One Health" perspective to synthesize the published data and identify knowledge gaps. Methods/principal findings We searched nine databases to identify articles relevant to four key aspects of C. burnetii epidemiology in human and animal populations in Africa: infection prevalence; disease incidence; transmission risk factors; and infection control efforts. We identified 929 unique articles, 100 of which remained after full-text review. Of these, 41 articles describing 51 studies qualified for data extraction. Animal seroprevalence studies revealed infection by C. burnetii (≤13%) among cattle except for studies in Western and Middle Africa (18-55%). Small ruminant seroprevalence ranged from 11-33%. Human seroprevalence was <8% with the exception of studies among children and in Egypt (10-32%). Close contact with camels and rural residence were associated with increased seropositivity among humans. C. burnetii infection has been associated with livestock abortion. In human cohort studies, Q fever accounted for 2-9% of febrile illness hospitalizations and 1-3% of infective endocarditis cases. We found no studies of disease incidence estimates or disease control efforts. Conclusions/significance C. burnetii infection is detected in humans and in a wide range of animal species across Africa, but seroprevalence varies widely by species and location. Risk factors underlying this variability are poorly understood as is the role of C. burnetii in livestock abortion. Q fever consistently accounts for a notable proportion of undifferentiated human febrile illness and infective endocarditis in cohort studies, but incidence estimates are lacking. C. burnetii presents a real yet underappreciated threat to human and animal health throughout Africa.